The quality standards and marketing techniques of hamburger restaurants in Iloilo - Abrasado, Kresyl Joy.; Dela Cruz, Mark.; Ildesa, Mirriam; Perualila, Nejema; Reyes, Anne Camille; Subong, Daniel; Tuson, Paul Anthony (2015.)
Iloilo City is home for many burger restaurants like Z Burger, Perri Todds, Stuckers Resto, American Legacy and many more. The city continues to occupy both existing and emerging burger restaurant that compete with eaxh other and against other businesses in the food industry. This research study focuses on three burger rastaurants namely Glor's Hamburger and broadway Cafe, Perri Todds All American Burger Company and Stuckers Resto. This will determine each burger restaurant's company profile, quality standards and marketing techniques. The study aims to compare the three burger restaurants based on several factors. The data were gathered through in depth interview and observation in each burger restaurants. Customer feedback was also acquired through surveys in the form of questionnaires with 30 respondents using random sampling. As a result, Glor's Hamburger and Broadway Cafe shows great difference when it comes to several factors in their profiles, quality standards and marketing techniques compared to Perri Todds and Stuckers Resto. Survey shows that customers value the variation of products and service quality in evaluating burger restaurants. As such, Perri Todds acquired greater preference with regards to familiarity, frequently visited and food quality among the three burger restaurants. Hence, consumers have different factors where they depend their preferences in choosing the product or service to buy. In the study, consumers tend to know and familiarize with the products from families, friends, colleagues, etc. They based their preferences to what is trendy and popular. The study also concludes that food and service quality matters greatly compared to the number of years of business.
[Research Paper -- Iloilo City : University of the Philippines Visayas, College of Management], November 2015.